1997
DOI: 10.1097/00003643-199707000-00004
|View full text |Cite
|
Sign up to set email alerts
|

Ondansetron, droperidol and their combination for the prevention of post-operative vomiting in children

Abstract: Ondansetron, droperidol and their combination for the prevention of post-operative vomiting in children Summary antiemetic prophylaxis. The differences between group N and all other groups were significant In this study the antiemetic effects of droperidol, on-(P<0.001). However, there were no statistically sigdansetron and their combination were evaluated in nificant differences between the groups D, O and 160 ASA Grade I and II children undergoing surgery D+O. It is concluded that droperidol (75 g kg −1 ) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(18 citation statements)
references
References 16 publications
1
17
0
Order By: Relevance
“…A subgroup analysis was conducted for 26 RCTs involving 4,878 patients in which the agents were administered during surgery [40, 43, 45, 53, 59, 74, 78, 79, 83, 86–89, 97, 102, 112, 113, 115, 117, 119, 123, 125, 132, 138, 142, 150]. The results were the same as for the primary analysis, except that significantly fewer patients of all ages receiving dolasetron experienced arrhythmia compared with placebo (OR 0.58, 95 % CI 0.36–0.93) and ramosetron (OR 0.38, 95 % CI 0.17–0.92) (Additional file 1: Appendix 13).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A subgroup analysis was conducted for 26 RCTs involving 4,878 patients in which the agents were administered during surgery [40, 43, 45, 53, 59, 74, 78, 79, 83, 86–89, 97, 102, 112, 113, 115, 117, 119, 123, 125, 132, 138, 142, 150]. The results were the same as for the primary analysis, except that significantly fewer patients of all ages receiving dolasetron experienced arrhythmia compared with placebo (OR 0.58, 95 % CI 0.36–0.93) and ramosetron (OR 0.38, 95 % CI 0.17–0.92) (Additional file 1: Appendix 13).…”
Section: Resultsmentioning
confidence: 99%
“…Another subgroup analysis was conducted for nine RCTs involving a total of 1,572 patients to examine the intra-operative administration of ondansetron, ondansetron plus dexamethasone, and granisetron plus dexamethasone to children (Table 3, Additional file 1: Appendix 13) [53, 79, 86, 89, 97, 113, 117, 123, 138]. Significantly more children receiving granisetron plus dexamethasone during surgery experienced arrhythmia compared with placebo (OR 5.15, 95 % CI 1.33–19.91), ondansetron (OR 4.71, 95 % CI 1.08–20.46), and ondansetron plus dexamethasone (OR 7.12, 95 % CI 1.66–30.63).…”
Section: Resultsmentioning
confidence: 99%
“…Our secondary endpoints were the incidence of POV and the incidence of OCR. Strabismus surgery is often associated with a remarkable high rate of PONV [43]. The reasons for the fairly high rates of PONV are not, as yet, understood.…”
Section: Discussionmentioning
confidence: 99%
“…[61] PONV prophylaxis with ondansetron was more effective than droperidol IV in children and was associated with less drowsiness, delayed discharge and extrapyramidal adverse effects. [62] The preferential use of ondansetron in this patient population may be justified, even though some authors observed that the use of ondansetron alone or in combination with droperidol was not superior to droperidol alone. [62] In one study, however, IV ondansetron 100 μg/kg in combination with IV droperidol 15 μg/kg administered at induction and at the end of the operative procedure was more effective than either drug given alone in reducing PONV after strabismus surgery.…”
Section: Ondansetronmentioning
confidence: 99%
“…[62] The preferential use of ondansetron in this patient population may be justified, even though some authors observed that the use of ondansetron alone or in combination with droperidol was not superior to droperidol alone. [62] In one study, however, IV ondansetron 100 μg/kg in combination with IV droperidol 15 μg/kg administered at induction and at the end of the operative procedure was more effective than either drug given alone in reducing PONV after strabismus surgery. [39] Ondansetron 100 μg/kg IV has been compared with droperidol 75 μg/kg and placebo in children undergoing dental surgery.…”
Section: Ondansetronmentioning
confidence: 99%